HPV AND ANAL CANCER: GLOBAL PATTERNS, KEY RISK FACTORS, AND ADVANCES IN PREVENTION - Maria Kubas; Katarzyna Krzemińska; Julia Kuszneruk; Julia Czerwik; Wojciech Kubas; Aleksandra Sadok; Patrycja Felisiak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: This article comprehensively analyzes human papillomavirus (HPV) in anal cancer, covering its epidemiology, etiology, risk factors, and role in anal squamous cell carcinoma.Methods: A literature search of PubMed and Google Scholar (2020–2025) included observational studies, clinical trials, meta-analyses, and systematic reviews.State of Knowledge: HPV is the main cause of anal squamous cell carcinoma (ASCC), whose incidence is rising in high-income countries and is highest in men who have sex with men (MSM), people with HIV, and those with multiple partners, immunosuppression, receptive anal intercourse, smoking, or co-infections. Over 80% of ASCC cases are linked to HPV16, with HPV-positive cancers showing better survival, yet despite the vaccine being nearly 100% effective if given before sexual debut, global uptake remains low.Conclusion: Persistent infection with high-risk HPV, especially HPV16, is the main driver of anal carcinogenesis, paralleling cervical disease, and HPV-driven anal cancer is an increasing public health concern. To reduce the incidence and improve outcomes, expanded vaccination, targeted screening, and public awareness are essential. Future efforts should focus on enhancing prevention uptake, clarifying the significance of HPV16 sublineages, and evaluating co-infections and immunity to improve prevention and management.